2021
DOI: 10.25259/sni_514_2021
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular empyema associated with severe pyogenic meningitis in COVID-19 adult patient: Case report

Abstract: Background: Coronavirus Disease 2019 (COVID-19) pandemic raised global attention especially due to the severe acute respiratory symptoms associated to it. However, almost one third of patients also develop neurological symptoms. The aim of the present study is to describe the case of a previously health adult that evolved cerebral ventricular empyema in the IV ventricle during COVID-19 infection treatment. Case Description: A 49-year-old man with COVID-19 developed pneumonia caused by multidrug-resistant A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 23 publications
(47 reference statements)
0
5
0
2
Order By: Relevance
“…A literature review identified 608 relevant articles using the above search terms. Of these, 5 papers described purulent intracranial infections directly associated with COVID-19 infections: 2 adult case reports and 3 paediatric [13][14][15][16][17]. Clinical data for these reports are summarised in Table 3.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A literature review identified 608 relevant articles using the above search terms. Of these, 5 papers described purulent intracranial infections directly associated with COVID-19 infections: 2 adult case reports and 3 paediatric [13][14][15][16][17]. Clinical data for these reports are summarised in Table 3.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One patient initially developed hydrocephalus secondary to meningitis while in ICU being treated for COVID-19 pneumonia; only on internalisation of a ventriculoperitoneal shunt and subsequent deterioration was the empyema diagnosed [14]. Across 3 patients, the COVID-19 diagnosis preceded identification of empyema diagnosis by 20-54 days [13,14,17]; in 2 patients, the diagnoses of empyema and COVID-19 were concurrent [15,16]. Empyemas reported in the literature were convexity (n = 3), parafalcine (n = 1), and intraventricular (n = 1) [13][14][15][16][17] (Table 3).…”
Section: Literature Reviewmentioning
confidence: 99%
“…We present below a summary of studies on carbapenemase-producing Enterobacteriaceae and A. baumannii in COVID-19 patients. Regarding P. aeruginosa , and while this multiresistant pathogen is known to produce carbapenemases (VIM-2, GES-7, VEB-1, IMP-1, KPC-2, PER-1) ( Cantón et al., 2020 ), and despite being among top pathogens co-infecting COVID-19 patients ( Ramadan et al., 2020 ; Senok et al., 2021 ; Westblade et al., 2021 ), sometimes associated with severe pyogenic infection ( Meguins et al., 2021 ), literature has not yet extensively reported carbapenemases from this organism in COVID-19 patients. This calls for vigilant investigations to fill such gap of knowledge regarding this significant nosocomial pathogen.…”
Section: Carbapenemase-producers Causing Co-infections In Covid-19 Pa...mentioning
confidence: 99%
“…Однако абсцесс или эмпиема головного мозга у пациентов с COVID-19 -редкие осложнения. Описано лишь несколько подобных случаев [3,4,9].…”
Section: пролиферация соединительнотканных элементов диапедезное проп...unclassified
“…В 8 % случаев COVID-19 может сопровождаться развитием бактериальной или грибковой инфекции [2]. В интернетресурсе PubMed (https://pubmed.ncbi.nlm.nih.gov / ) найдено всего несколько описаний развития бактериального менингита у взрослых пациентов с COVID-19 [3][4][5]. Каких-либо обобщающих исследований в этой области не найдено.…”
Section: Introductionunclassified